2012
DOI: 10.1002/hep.24724
|View full text |Cite
|
Sign up to set email alerts
|

Dual therapy with the nonstructural protein 5A inhibitor, daclatasvir, and the nonstructural protein 3 protease inhibitor, asunaprevir, in hepatitis C virus genotype 1b–infected null responders

Abstract: Patients with chronic hepatitis C virus (HCV) infection and previous null response to pegylated interferon (Peg-IFN) and ribavirin (RBV) have limited therapeutic options. HCV genotype 1 is the most common worldwide and the most difficult to treat; genotype 1b is the most common subtype of genotype 1 outside North America. The enhanced antiviral activity achieved by combining two direct-acting antiviral (DAA) agents may improve clinical outcomes. This open-label, phase IIa study included 10 patients with chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
272
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(284 citation statements)
references
References 29 publications
9
272
1
2
Order By: Relevance
“…Safer and more effective HCV regimens may improve the prognosis of C-HCC. [34][35][36] A previous study also revealed the improved prognosis of B-HCC over time. However, that study included patients treated with surgery, ablation therapies and TACE.…”
Section: Discussionmentioning
confidence: 89%
“…Safer and more effective HCV regimens may improve the prognosis of C-HCC. [34][35][36] A previous study also revealed the improved prognosis of B-HCC over time. However, that study included patients treated with surgery, ablation therapies and TACE.…”
Section: Discussionmentioning
confidence: 89%
“…40,41 Response rates in prior null responders, as reported in one of the trials, were 100%; in the other trial, response rates of 63.6% and 90.5% were reported in PegIFN intolerant/ineligible (n ¼ 22) and null-responder (n ¼ 10) patients, respectively. 40,41 Of note, in these Japanese phase 2 trials asunaprevir dose was adjusted from 600 mg twice daily to 200 mg twice daily due to observed hepatotoxicity at higher doses. 43 The U.S. study investigated different dosing regimens of asunaprevir (200 mg twice daily vs. 200 mg once daily) in HCV genotype1b null-responders without cirrhosis: SVR rates ranged from 65 to 78%.…”
Section: Clinical Trials Investigating the Combination Of A Ns3/4a Prmentioning
confidence: 96%
“…Therapeutic efficacy of this dual DAA regimen administered for 24 weeks was further investigated in several phase 2 trials conducted in Japan and in the United States. [40][41][42] Two Japanese studies enrolled HCV genotype 1b patients without cirrhosis who were intolerant/ineligible and/or nullresponder patients. 40,41 Response rates in prior null responders, as reported in one of the trials, were 100%; in the other trial, response rates of 63.6% and 90.5% were reported in PegIFN intolerant/ineligible (n ¼ 22) and null-responder (n ¼ 10) patients, respectively.…”
Section: Clinical Trials Investigating the Combination Of A Ns3/4a Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Many NS5A inhibitors are now undergoing clinical trials. A trial of combination therapy with NS5A inhibitor (BMS-790052) and NS3/4A PI (BMS-650032) in Japanese HCV G1b patients with prior null response to PEG-IFN plus RVB therapy revealed extremely high SVR rates [58]. In contrast, the efficacy of this combination is discouraged in American HCV G1a patients that were previously null responders.…”
Section: Ns5a Inhibitorsmentioning
confidence: 99%